2023
DOI: 10.3390/brainsci13081182
|View full text |Cite
|
Sign up to set email alerts
|

Executive Attentional Dyscontrol as a Core Cognitive and Behavioral Feature of Individuals with Obesity and Cardiovascular Disease: A Cross-Sectional Investigation

Abstract: Executive attention as a frontal domain ability that is effective in potentially blocking distracting information, reconciling conflicts among simultaneous attentional demands, and regulating impulsive behavior may be impaired in individuals with obesity and cardiovascular disease (CVD). This study aimed (i) to explore the presence of selected cognitive (global cognitive impairment, sensitivity to interference, and attention) and psychological (quality of life, depression, anxiety, and impulsivity) dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…Still, these results should be interpreted considering that the large majority of the sample had obesity as a comorbidity, and, as shown in previous studies [55], both motor and attentional impulsiveness are hard to detect in overweight or obese patients.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Still, these results should be interpreted considering that the large majority of the sample had obesity as a comorbidity, and, as shown in previous studies [55], both motor and attentional impulsiveness are hard to detect in overweight or obese patients.…”
Section: Discussionmentioning
confidence: 54%
“…The findings of this study also suggest that BMI negatively correlated with the perceived QoL of the sample, although this association was less strong than those that QoL was shown to have with anxiety and depressive symptoms. Accordingly, evidence exists for the negative impact of a higher BMI on the QoL of individuals, and obesity was associated with the causal promotion of CVD in different studies [23,55,91]. When entered into the regression model, BMI alone significantly predicted 11.8% of the variance in QoL, which increased to 18.4% when impulsiveness was added to the model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Suboptimal executive functions, impaired decision-making, and impulsivity are frequently associated with addictions-of particular interest for us is food addiction [72]. Obese patients with cardiovascular disease showed a lower level of sensitivity to cognitive interference, lower abilities in divided attention during visual-tracking tasks, and greater impulsivity than normal-weight cardiovascular patients (as manifestations of attentional and executive dyscontrol) [73]. In another study, obese patients showed impaired performance on the decision-making task (Iowa gambling task) and performed the worst on the set-shifting task (Wisconsin Card Sorting Test).…”
Section: Cognitive Ability Domainsmentioning
confidence: 99%